Natural Relief for Allergies: An Overview - Chaudhary, Hema; Rathee, Permender; Rathee, Sushila; Kumar, Vikash (Pharmacognosy Reviews)
An allergy is an overreaction of the immune system to a substance called an antigen, something that is foreign to the body but otherwise harmless (e.g., pollen from grasses and flowers, etc.). In an allergic individual, the harmless antigen becomes an allergen (a substance that initiates an allergic reaction). The symptoms of allergic reactions may include sneezing, watery eyes and nasal congestion, as in hay fever and allergic rhinitis; a rash, upset stomach and itchy swellings on the skin (hives), as with some food or drug allergies; or spasms within the lungs that interfere with breathing, as in allergic asthma. According to a latest study conducted in the United States, "Allergies affect around 20% of Americans while asthma affects an estimated 17 million people in the U.S. alone". Allergy or hypersensitivity is a reaction of our immune system in response our body's contact with harmful allergens. In the present review an attempt has been made to explore different herbal plants individual or in combination (Scutellaria baicalensis, Picrorhiza kurroa, Echinacea, Aller-7 etc) having anti-allergic properties, useful in the treatment of allergic conditions.
Keywords: Allergy; Scutellaria baicalensis; Picrorhiza kurroa; Aller-7; Echinacea; Anti-allergy